PENGARUH LIVE STREAMING, PERSEPSI HARGA, E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE - Octavia, Stevany; Yusrin, Nur Amalyna (Publika Citra Media, 2025)
The purpose of this study is to analyze the influence of live streaming, price and e-commerce on purchasing decisions. Quantitative method with survey approach was chosen for this study. This study relies on data obtained through the distribution of internet-based questionnaires with 170 sample participants. In this study, the independent variables are live streaming, price and e-commerce and purchasing decisions that function as dependent variables. PLS-Sem (Partial Least Squares Structural Equation Modeling) used to process the data is SmartPLS 3.0 software. Based on the results of the study, it is known that the three independent variables simultaneously have an influence on purchasing decisions, but the magnitude of the influence shown is still relatively low. Partially, live streaming has the greatest influence compared to price and e-commerce. This confirms that direct communication between sellers and consumers can create trust, interest, and accelerate the decision-making process.